Ergosterol alleviates hepatic steatosis and insulin resistance via promoting fatty acid β-oxidation by activating mitochondrial ACSL1 - Zu-Guo Zheng; Yi-Ping Zhang; Xiao-Yu Zhang; Meng-Yao Qin; Yin-Yue Xu; He Wu; Run-Qing Liu; Qiu-Yi Wu; Ming-Su Wang; Chong Zhang; Yue-Qin Zheng; Jian-Ye Dai; et al. (Cell Reports)
Summary: Sterols target sterol-sensing domain (SSD) proteins to lower cholesterol and circulating and hepatic triglyceride levels, but the mechanism remains unclear. In this study, we identify acyl-coenzyme A (CoA) synthetase long-chain family member 1 (ACSL1) as a direct target of ergosterol (ES). The C-terminal domain of ACSL1 undergoes conformational changes from closed to open, and ES may target the drug-binding pocket in the acetyl-CoA synthetase-like domain 1 (ASLD1) of ACSL1 to stabilize the closed conformation and maintain its activity. Moreover, ES is mainly enriched in the mitochondria and promotes fatty acid β-oxidation through ACSL1 allosteric activation. Structure-activity relationship analysis reveals how different structural sterols interact with the sterol-sensing domain-containing protein (SCAP) and ACSL1, explaining their regulatory effects on lipid metabolism. Moreover, our findings reveal that the combination of SCAP inhibitor 25-hydroxycholesterol (25-HC) and ES has a stronger lipid-lowering effect than alone.